2018
DOI: 10.1371/journal.pone.0202995
|View full text |Cite
|
Sign up to set email alerts
|

Coral connectivity between equatorial eastern Pacific marine protected areas: A biophysical modeling approach

Abstract: There are many marine protected areas (MPAs) containing coral reef aggregations in the eastern Pacific region. However, the connectivity of corals between MPAs is still poorly known, especially in the Marine Conservation Corridor of the Eastern Tropical Pacific (MCCETP). Here, we assess the potential connectivity of corals across equatorial eastern Pacific MPAs through a Lagrangian particle-tracking algorithm coupled offline with an ocean-circulation numerical model. Connectivity metrics and graph theory were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…, Lequeux et al. ), those assuming constant stochastic loss rates likely overestimate it (e.g., Connolly and Baird , Thomas et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Lequeux et al. ), those assuming constant stochastic loss rates likely overestimate it (e.g., Connolly and Baird , Thomas et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas long-distance dispersal estimates assuming rectangular competence curves likely underestimate long-distance dispersal (e.g., Treml et al 2008, Lequeux et al 2018, those assuming constant stochastic loss rates likely overestimate it (e.g., Baird 2010, Thomas et al 2014). The discrepancy is important, given that, for instance, the tail of the dispersal kernel may be crucial for determining potential rates of movement of potentially adaptive genotypes in the face of rapid environmental change.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a biophysical model, Lequeux et al (2018) suggested that the islands of Malpelo and Gorgona serve as "stepping stones" between the mainland and offshore islands, such as the Galapagos. This suggests that the record of E. minutus from Santa Cruz Island might be the result of quasi-unidirectional larval flow from the continent to oceanic islands in the equatorial eastern Pacific.…”
Section: Discussionmentioning
confidence: 99%
“…), which may vary inter-annually, seasonally and in short term. Rapidly developing field of research, that aims to resolve how physically driven connectivity should be taken into account in designating marine protected area networks, is the graph theoretic approach and network analysis (Treml et al 2008;Kininmonth et al 2011Kininmonth et al , 2019Krueck et al 2017;Treml and Kool 2018;Fox et al 2019;Friesen et al 2019), which can be coupled with oceanographic and biophysical modelling that integrates the physics of the ocean and the characteristics of species (Watson et al 2012;Thomas et al 2014;Lequeux et al 2018), including the effects of larval traits and habitat quality (Berglund et al 2012;Corell et al 2012;Jonsson et al 2016;Magris et al 2016).…”
Section: Introductionmentioning
confidence: 99%